Stock Prices Predicted by Bankruptcy Condition? - Junaeni, Irawati (Binus Business Review, 2018)
This research had two objectives. First, it determined the prediction of the method of Altman Z-Score whether it could classify banking positions, bankruptcy, or financial distress in the go-public bank in Indonesia Stock Exchange. Second, it was to know the influence of value position of Altman Z-Score on the stock price. The population was 84 banking company listed on the Indonesia Stock Exchange in 2010-2015. The sampling method was purposive sampling. Moreover, data analysis method used was a simple regression analysis. For data processing, it used software Eviews 8. The Z-Score calculations predict the potential bankruptcy of go-public bank in 2010-2015. All results show that Z-Score has the small score of 1,81. It can be said there is a potential bankruptcy. For t-test, it can be concluded that Z-Score has the positive and significant effect on the stock price. The ability of Z-Score values in explaining the stock price is 95,50% while the remaining 4,50% is influenced by other variables that are not analyzed in the research. With some weaknesses of Altmanâs Z-Score model, this research has the implication for management bank. It improves the financial performance for the future to avoid opportunity bankruptcy prediction. The results show how the effect of bankruptcy on banking stock prices.